Where we go from here : two years in the resistance - Sanders, Bernard (Thomas Dunne Books, St. Martin's Press, 2018)
The Democratic presidential candidate, popular senator, and respected economist traces the first year of the Trump administration and what Sanders and his followers are doing to reinforce the progressive movement.